Ligas bimetálicas magnéticas à base de metais de transição (Ni, Fe e Co) como eletrocatalisadores altamente eficientes para Reação de Evolução de Oxigênio - Raimundo, Rafael Alexandre (2021)
The need for renewable and clean fuels, such as hydrogen gas (H2) has attracted considerable interest in recent years. In this context, water electrolysis (water splitting) is capable of producing these gases through two semi-reactions, OER (Oxygen Evolution Reaction) and HER (Hydrogen Evolution Reaction). Thus, this work presents an experimental study of bimetallic magnetic alloys based on transition metals (Ni, Fe and Co) that were produced by two synthesis methodologies, Solution Blow Spinning (SBS) and Sol-gel Proteic (SG), with nanofibers and nanoparticles nanostructures, respectively. These bimetallic alloys have potential application in electrocatalysts for OER in an alkaline medium. A total of seven samples were produced, three by SBS (NiFe-NiFe2O4, NiFe-carbon and Fe0,5Co0,5-Co1,15Fe1,15O4/carbon) and four by SG (NiFe-500, NiFe-700, CoFe2/CoFe2O4 and CoFe2). Elementary and advanced characterization techniques, such as scanning and transmission electron microscopes, X-ray dispersive energy spectroscopy, X-ray diffraction with Rietveld refinement, X-ray photoelectron spectroscopy, Mössbauer spectroscopy, magnetization measurements in the function of field (MXH) and temperature (MXT), linear-cyclic voltammetry (LSV and CV) and electrochemical impedance spectroscopy (EIS) have been applied to provide a detailed understanding of the morphological, structural, magnetic and electrochemical properties of bimetallic alloys produced. The fibers produced by SBS had an average diameter ranging from 51-1503 nm, while the nanoparticles dispersed in the carbonaceous matrix have an average diameter ranging from 7-55 nm. The size distribution of the nanoparticles produced by SG is in the range of 30-588 nm. X-ray diffraction confirms the polycrystalline characteristic of the samples; crystallite sizes ranged from 7-64 nm. Mössbauer spectroscopy, a technique for identifying chemical species using gamma radiation, confirms the formation of bimetallic alloys. From the electrochemical point of view, the CoFe2 sample produced by SG presents the smallest superpotential at 10 mA cm-2, η = 288 mV, followed by NiFe-carbon samples (η = 296 mV, produced by SBS), CoFe2/CoFe2O4 (η = 304 mV, produced by SG), NiFe-700 (η = 307 mV, produced by SG), Fe0,5Co0,5-Co1,15Fe1,15O4/carbon (η = 308 mV, produced by SBS), NiFe-NiFe2O4 (η = 316 mV, produced by SBS) and NiFe-500 (η = 319 mV, produced by SG). All samples have excellent chemical/mechanical stability of the electrodes. In addition, it was observed that the magnetic properties, such as saturation magnetization (MS), remnant magnetization (MR), coercivity (Hc) and Curie temperature (TC), depending on the atomic amount of Ni, Fe and Co contained in the alloys, as well as, of the present phases and crystalline structures formed. The magnetic results showed that alloys produced by the Sol-gel proteic route have greater saturation magnetization (Ms): 226 emu/g for CoFe2, 196 emu/g for CoFe2/CoFe2O4, 173,6 emu/g for NiFe-700, 164,2 emu/g for NiFe-500, 116 emu/g for NiFe-NiFe2O4 and 30,2 emu/g for NiFe-carbon. From the MXT curves, the blocking temperatures (TB) of the NiFe-NiFe2O4 and NiFe-carbon samples were determined to be 117 and 115 K, respectively. The NiFe-NiFe2O4 sample showed improved magnetic permeability, that is, rapid response to small variations in the magnetic field. In general, it is observed that nanoparticles have the best catalytic activities and magnetic properties, in particular, the CoFe2 sample, which has the lowest superpotential (η = 288 mV) and the highest saturation magnetization (Ms = 226 emu/g).